Effect of the solvent in the catalyst ink preparation on the properties and performance of unsupported PtRu catalyst layers in direct methanol fuel cells. (20th March 2017) - Alcaide, Francisco; Álvarez, Garbiñe; Cabot, Pere L.; Genova-Koleva, Radostina; Grande, Hans-Jürgen; Miguel, Oscar
Abstract: The effect of the organic solvent polarity on the properties of unsupported PtRu catalyst inks and on the performance of the catalyst layers prepared with them for the methanol electrooxidation, has been studied. The light scattering results indicate that the PtRu-Nafion ® aggregates in the inks prepared with n-butyl acetate (NBA) are larger than those prepared with 2-propanol (IPA). The lower polarity of the former favours the aggregation of Nafion ® and nanoparticles. The electron microscopy images and porosimetry measurements of the catalyst layers show that the secondary pore volume between the agglomerates is larger for NBA. The linear sweep voltammetry and eis results for the methanol electrooxidation in the three-electrode cell denote the higher active surface area for NBA and comparable specific oxidation rates of the intermediates in both catalysts layers. The current densities for PtRu anode catalyst layers in single DMFC are higher when the solvent is NBA, the mass transport limitations being much more apparent with IPA. The adapted transmission line equivalent circuit to interpret the impedance results in single DMFC indicates that the proton resistance for NBA is significantly lower than for IPA, thus suggesting that the greater number of accessible active sites for methanol oxidation in the former are well connected to the Nafion ® ionomers and easier transported to the membrane.